A new immunohistochemical marker, insulinoma-associated protein 1 (INSM1), for Merkel cell carcinoma: Evaluation of 24 cases - CİNEL, ZELİHA LEYLA (ELSEVIER SCIENCE INC, 2019)
Merkel cell carcinoma (MCC) is an uncommon primary neuroendocrine carcinoma of the skin. Nowadays, pathologists are required to perform immunohistochemistry to demonstrate neuroendocrine and epithelial differentiation for diagnosis of MCC. Insulinoma-associated protein 1 (INSM1) is a zinc-finger transcription factor expressed in tissues undergoing terminal neuroendocrine differentiation, and INSM1 immunohistochemistry is a well-validated nuclear marker of neuroendocrine differentiation. We evaluated 24 cases of MCC for the expression of INSM1 and compared it with frequently used neuroendocrine markers, Chromogranin A, Synaptophysin, and CD56. INSM1 was positive in all cases, and its expression was stronger, more extensive, clean and homogeneous compared to other markers. As a consequence, INSM1 can be used to serve as a solitary marker for neuroendocrine differentiation due to high sensitivity and specificity in MCC cases.
Keywords: Merkel cell carcinoma; Neuroendocrine carcinoma of the skin; INSM1; Synaptophysin; Chromogranin; CD56; DIFFERENTIAL-DIAGNOSIS; NEUROENDOCRINE TUMORS; EXPRESSION; CD56